IMPLEMENTING SQ3R STRATEGY TO IMPROVE THE READING COMPREHENSION OF GRADE XI OF SMAS NU CENTINI LAREN LAMONGAN - Zanuba Arifah Khofshoh (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2016)
Reading is the most useful skill and has an important role in humanbeing’s life. Through reading, everyone can get information about science, andtechnology that perhaps they do not know before.This study is aimed atimproving the ability of grade XI of SMAS NU Centini Laren Lamongan inreading comprehension by implementing SQ3R strategy. This strategy is chosenbased on the effective stages in encouraging and having the students involve inteaching learning process of reading comprehension. This study wasimplemented in two cycles, in which the first cycle was carried out in threemeetings and the second cycle also carried out three meetings. Theimprovement was indicated by the students’ achievement which increased frompreliminary study to the first reading comprehension test of Cycle 1 and in thereading comprehension test of Cycle 2 was well improved respectively. As aresult, it could be clearly stated that reading comprehension of grade XIstudents of SMAS NU Centini be improved by using SQ3R strategysignificantly. Keywords: Implementation, SQ3R strategy, Reading comprehension.